(untitled) (Perspectivas de las Ciencias Económicas y Jurídicas, 2023)
The article analyzed the controversy between Thirlwall and Krugman over the elasticities of international trade that he took up with the conferences that Thirlwall gave in Mexico in 2003 at UNAM, where he pointed out that Krugman never that his recognized article of 1989 has its roots in his work of 1979, although that one was referenced in Houthakker and Magee (1969). After reviewing Thirlwall’s Law and Krugman’s empirical regularity, the work offers an explanation for the controversy between both economists, describing the differences and commonalities of both approaches, along with an empirical application where both models are validated in Latin America between 1993-2016.